O067 Efficacy and safety of interventional therapy of low-flow vascular malformations based on the experience from a single specialist centre. (22nd July 2022) - Pang, C; Arasakumar, DRB; Evans, N; Papadopoulou, A; Khalifa, M; Hamilton, G; Brookes, J; Lim, CS
Abstract: Introduction: To evaluate the efficacy and safety of embolo-sclerotherapy (EST) of low-flow vascular malformations (LFVM) in a specialist vascular anomalies centre. Methods: All patients with LFVM who underwent EST from 01 January 2015–31 December 2019 were retrospectively reviewed. All ESTs were performed with foam STS 3%, ethanol, coils and/or other substances e.g. triamcinolone. LFVMs were grouped according to Puig's classification. The outcome measures were treatment effects and complications. Continuous variables were compared using ANOVA test. Other discrete variables were compared using Chi-squared tests. Differences were considered significant at P<0.05. Results: A total of 207 patients, with a mean age of 32 years (range 1–71 years) were included. The use of EST with foam STS was significantly lower for type I LFVM (61.8%) compared to others (p<0.001). However, significantly higher type I LFVM (26.5%) were treated with surgery than EST (p<0.001). Overall, outcome categories were significantly different across all types of LFVM (p<0.001), with more discharges for Type I (52.9%) LFVMs but more failure to follow-up in patients with Type II (24.5%) LFVM. EST complications was significantly higher with type I (14.7%) LFVMs (p=0.030). The doses of STS in the first procedure were significantly different across all types of LFVM (p<0.001) with most type I LFVM patients receiving ≤2 ml. Conclusion: EST particularly with foam sclerotherapy is clinically effective and safe for patients with LFVM especially in those with Puig's Type I and II lesions. This classification may provide an important guide to volume of sclerosant required and the potential success rate. Take-home message: EST particularly with foam sclerotherapy is clinically effective and safe for patients with LFVM especially in those with Puig's Type I and II lesions. This classification may provide an important guide to volume of sclerosant required and the potential success rate.